Pursed-Lip Breathing as a Belief-Based Nursing Intervention to Reduce Respiratory Rate in Patients with Pulmonary Tuberculosis: A Narrative Literature Review - Fernando Da Costa Fernandes; Indah Sri Wahyuningsih; Dwi Heppy Rochmawati; Erna Melastuti (International Journal of Pharmaceutical and Bio Medical Science, 2026)
Background: Pulmonary tuberculosis remains a major global health concern and is frequently accompanied by increased respiratory rate due to impaired lung function. Non-pharmacological nursing interventions that incorporate patients’ belief systems may enhance physiological and psychological outcomes. Objective: This review aims to examine the effectiveness of pursed-lip breathing as a belief-based nursing intervention in reducing respiratory rate among patients with pulmonary tuberculosis. Methods: A narrative literature review was conducted by analyzing studies published between 2020 and 2026. Literature was obtained from PubMed, Google Scholar, ScienceDirect, DOAJ, and Garuda using relevant keywords. Articles were selected based on predefined inclusion criteria, and a total of 7 studies were analyzed using a descriptive approach. Results: The findings show that pursed-lip breathing consistently contributes to a reduction in respiratory rate by improving ventilation efficiency and prolonging the expiratory phase. When integrated with belief-oriented nursing care, such as spiritual support or culturally relevant practices, patients demonstrated better adherence, reduced anxiety, and more stable breathing patterns. Several studies reported significant improvements in respiratory parameters following the intervention. Discussion: The effectiveness of pursed-lip breathing is strengthened when aligned with patients’ beliefs, as it addresses both physiological and psychological dimensions of care. This integrative approach supports patient-centered nursing practice and enhances overall therapeutic outcomes. Conclusion: Pursed-lip breathing, when applied as a belief-based nursing intervention, shows promising potential in reducing respiratory rates among patients with pulmonary tuberculosis, although further rigorous studies are needed to confirm its long-term effectiveness.